1997
DOI: 10.3748/wjg.v3.i4.231
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of different interventional therapies for primary liver cancer

Abstract: AIM:To compare the therapeutic effect of three types of interventional management for primary liver cancer. METHODS:A total of 468 patients with primary liver cancer were randomly allocated to the following three groups: 138 cases treated with chemotherapy alone using mitomycin C, adriamycin and 5-FU (group A); 158 cases treated with chemoembolization using lipiodol (group B); and 172 cases with chemoembolization using lipiodol and gelfoam (group C). All patients were angiographically and sonographically follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The possible participants should be restricted to the patients at early stage of HCC. However, another two included papers by Eurvilaichit and Liu did not conduct any subgroup analyses (Eurvilaichit and Kanjanapitak, 2000;Liu et al, 2007). Therefore, future studies should confirm the findings in such patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The possible participants should be restricted to the patients at early stage of HCC. However, another two included papers by Eurvilaichit and Liu did not conduct any subgroup analyses (Eurvilaichit and Kanjanapitak, 2000;Liu et al, 2007). Therefore, future studies should confirm the findings in such patients.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, 2037 papers were initially retrieved, of which 3 were included (Eurvilaichit and Kanjanapitak, 2000;Lee et al, 2002;Liu et al, 2007) (Figure 1). Study characteristics were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Lipiodol and gelatin sponge are common embolizing agents used in TACE [ 37 ]. Some reports have suggested that TACE, when combined with lipiodol, is more effective than TAI or conservative treatment [ 22 , 38 ]. The effectiveness of the embolizing agents depends on their size.…”
Section: Nonsurgical Therapiesmentioning
confidence: 99%
“…MDR is the main cause for the failure of chemotherapy in the treatment of malignant tumors [13]. Besides, MDR also constitutes one of main reasons as to why the conventional, targeted arterial embolization interventional therapy fails in the chemotherapy of primary hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%